MODEL PEMBERDAYAAN PEREMPUAN NELAYAN DI KABUPATEN DEMAK (Studi Kasus di Desa Morodemak) - Tri Risandewi (JURNAL LITBANG PROVINSI JAWA TENGAH, 2014)
The aims of this research are describing the fisherwomen empowerment model and the supporting factors and the obstacles of the fisherwomen empowerment model in Morodemak Village-Demak Regency. From the research can be concluded that the fisherwomen in Puspita Bahari Morodemak village is the model of exploring business which is the final step of fisherwomen empowering through intregrated and effective technology implementation. The factors which enhance those models are the supports not only from the government but also from the private institusion and the society. There are some factors which slowen down them, the obstacle of having organization (materialistic and cultural obstacles, cultural patriarcy, and cultural inferiority). Morever the obstacles also can be found in the management (such as limited infrastructure machines, slicer, stoves, freezer and included the kitchen utensils and there is no production place), products distribution, and the unreachable price of the raw material for the production and the unpredictable fish whish is caught by the fishermen can be the most dangerous factors. In order to overcome those obstacles, there must be ways to help the fisherwomen in organization, improving their knowledge through training. The training can improve their knowledge in pre- production and post production in order to improve the quality of the products and can be accepted by many customers. Morever, the group of the fisherswomen needs to be given more capital, infrastructure, to run the business.